Establishment of reference intervals of oxidized low-density lipoprotein cholesterol in a population of West Bengal - Kapil Deb Lahiri,; Amit Kumar Gupta,; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2024)
Background: Elevated oxidized low-density lipoprotein (Ox-LDL) was significantly associated with the atherosclerotic cardiovascular disease as well as retinal vascular diseases but there were no studies to show the reference range of Ox-LDL levels in any Indian population. Aims and Objectives: The aim of this study was to formulate the reference intervals of Ox-LDL cholesterol in a population of West Bengal. Materials and Methods: Ox-LDL levels of 434 apparently healthy individuals were estimated based on the history, clinical examination, and laboratory investigations. Statistical analysis was performed using the statistical package for the social sciences software. Results: The reference range of Ox-LDL levels for all ages was 34.1±4.9 mol/L in healthy male and 34.5±4.5 mol/L in healthy female. The 2.5th and 97.5th percentile values of Ox-LDL level in the reference population were 27 (0.90 CI = 26.4–27.6) and 42 (0.90 CI = 41.4–42.6), respectively. Conclusions: Reference intervals for Ox-LDL may help clinicians to predict the future risk for coronary heart disease and retinal vascular disease by taking medical decision limits and also open up the scope for further research for other laboratories to formulate their own reference interval of Ox-LDL.